Feeding Practices and Nutritional Status of The Toddler - Marlina, Yessi; Erowati, Dewi; Yolahumaroh, Yolahumaroh (Poltekkes Kemenkes Riau, 2024)
Complementary feeding practices that are not optimal are one of the causing factors of stunting. The purpose of this study was to determine the relationship between complementary feeding practice and stunting among children in Kampar Districts. Complementary feeding practices include early age of giving complementary feeding, texture, frequency, portion, hygiene, and responsive feeding. Kampar is a high contributor to fish resources but has also been a locus for stunting for several years. The cross-sectional study with a population of all children aged 6-23 months. The proportionate stratified random sampling technique was used with a total sample is 100 children. Body length was measured using a length board, feeding practices were obtained through observation using a checklist sheet, and nutritional intake through food recall for 1x24 hours. Data analysis was univariate and bivariate using the chi-square test. There are 17% stunted and 83% non-stunted. As many as 29% received early complementary feeding, 70% texture was inappropriate, 66% frequency was inappropriate, 69% portion was inappropriate, 83% menu did not vary, 95% was not hygienic, 38% was unresponsive and inadequate intake. There was a significant relationship between responsive feeding and nutritional status (p<0.05)